Neglected and at risk: bryophyte diaspore banks of coastal dune systems. (2nd July 2020) - Callaghan, Des A.; During, Heinjo J.; Forrest, Laura L.; Wilkinson, Karen
ABSTRACT: Introduction. Bryophyte diaspore banks are virtually ubiquitous in soil environments but remain poorly known and rarely given attention during conservation planning. This study investigates the frequency and composition of bryophyte diaspore banks of coastal dune slacks and considers conservation implications. Methods. A total of 327 soil samples was collected from 28 slacks at eight coastal dune systems in Wales (UK), subjected to germination trials in a growth chamber. Identification of emergent species was based on morphology supplemented by DNA barcoding. Species composition of above ground bryophytes was recorded at a subset of locations and compared to the diaspore bank composition. Results and conclusions. Viable bryophyte diaspores can be abundant in dune slacks, ranging from long-lived perennials to short-lived ephemerals, representing significant phylogenetic diversity. Bryophytes grew in 211 (63%) samples, including 34 taxa identified to species level (7 liverworts and 27 mosses) and a further four to aggregate. Five species of conservation concern were detected. DNA barcoding was sometimes useful but often equivocal in helping to inform species determinations. Occurrence of germination across soil samples at 0–5 cm depth was very high (97%), declining sharply to 17% at 15–20 cm. Compared to species in surface vegetation of mature slacks, those in diaspore banks tend to have significantly smaller adult gametophytes and produce asexual propagules more often. Bryophyte diaspore banks need to be considered carefully when making conservation assessments and land-use decisions, and there is an urgent need for further research to help understand and manage this important resource.